Prospects of Plant-Based Trimethylolpropane Esters in the Biolubricant Formulation for Various Applications: A Review - Raof, Nurliyana A.; Hamid, Hamidah Abd; Mohamad Aziz, Nur Atiqah; Yunus, Robiah (Frontiers in Mechanical Engineering, 2022)
Biodegradable lubricants from renewable feedstocks have been successfully developed to meet the demands of new machines with stringent requirements of the global standards, which addressing sustainability and environmental policy. Trimethylolpropane ester (TMPE) has been extensively evaluated as a biolubricant base stock and occasionally used as an additive, due to their low toxicity and excellent biodegradability. The formulation of high-performance TMPE-based lubricants involves addition of surface additives, multifunctional additives, and solid nano particles. This review focuses on the development of plant-based TMPE formulation for various applications, namely food-grade lubricant, engine oil, drilling fluid, insulating fluid, metal working fluid, hydraulic and heat transfer fluids. Even though plant-based TMPE lubricants have huge advantages over mineral oils, they have other challenging issues such as limited load bearing capacity, hygroscopic properties and high risk of toxic emission owing to additives selection. The details on the performance characteristics of TMPE as base stocks and additives are discussed, including the current prospects and challenges in the respective areas. This review concludes with a brief discussion on suggestions and recommendations for future advancement in the usage of TMPE and the remaining issues that must be overcome to allow for its full potential to be realized.